Call the midwife. Season two [videorecording (DVD)] - Lowthorpe, Philippa; Payne, Jamie; Worth, Jennifer, 1935-2011; Raine, Jessica, 1982-; Ferris, Pam; George, Helen, 1984- (Warner Home Video, 2013)
Season Two continues to follow Jenny and the other midwives as they deal with all the problems the neighborhood of Poplar has to throw at them. A fascinating portrayal of birth, life, death and a community on the brink of huge social change, Call the Midwife offers a gripping insight into a way of life that is so drastically different from how we live now.